2022
DOI: 10.1186/s40001-022-00654-7
|View full text |Cite
|
Sign up to set email alerts
|

Serum cystatin C, kidney injury molecule-1, neutrophil gelatinase-associated lipocalin, klotho and fibroblast growth factor-23 in the early prediction of acute kidney injury associated with sepsis in a Chinese emergency cohort study

Abstract: Background Acute kidney injury (AKI) is a common and critical complication of sepsis, and is associated with unacceptable morbidity and mortality. Current diagnostic criteria for AKI was insensitive for early detection. Novel biomarkers including cystatin C, kidney injury molecule-1 (KIM-1), neutrophil gelatinase-associated lipocalin (NGAL), klotho and fibroblast growth factor-23 (FGF-23) can predict AKI earlier and allow immediate interventions. We aimed to determine the diagnostic performance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…The plasma LCN2 level was higher in AKI than in non-AKI septic patients, the AUCs of LCN2 for predicting AKI in septic patients were reported from 0.620 to 0.897 [31][32][33] . The lowest AUC was 0.620, with 95.6 ng/ml as the cutoff value, the sensitivity and speci city were 0.300 and 0.931, respectively 32 . The highest AUC was 0.897 31 .…”
Section: Discussionmentioning
confidence: 99%
“…The plasma LCN2 level was higher in AKI than in non-AKI septic patients, the AUCs of LCN2 for predicting AKI in septic patients were reported from 0.620 to 0.897 [31][32][33] . The lowest AUC was 0.620, with 95.6 ng/ml as the cutoff value, the sensitivity and speci city were 0.300 and 0.931, respectively 32 . The highest AUC was 0.897 31 .…”
Section: Discussionmentioning
confidence: 99%
“… 94–96 The process of growth and development is a lifelong journey involving physical, cognitive, emotional, and social development. 77 , 97 It is a complex and unique process for each individual, reflecting the interaction between biological, social, and psychological factors. Growth and development often involve changes in thinking, moving, and behaving.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, several novel biomarkers have been identified to detect kidney injury and predict the development of AKI. A Chinese emergency cohort study showed that serum cystatin C, kidney injury molecule-1, neutrophil gelatinase-associated lipocalin, klotho, and fibroblast growth factor 23 are valuable in the early prediction of sepsis-related acute kidney injury ( Pei et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%